AB0257 Influence of Upper Extremity Surgeries on the Improvement of Patients' Disease Activity and Activity of Daily Living in Patients with Rheumatoid Arthritis. (10th June 2014) - Hashizume, K.; Nishida, K.; Nakahara, R.; Harada, R.; Machida, T.; Ozaki, T.
Abstract : Background: Some population of patients with rheumatoid arthritis (RA) still suffer from physical dysfunction due to progressive joint destruction and deformity, even by the disease control with biologic agents. It has been accepted that orthopaedic surgeries on upper extremity for damaged joints provide favorable effects in terms of pain relief and better joint function. However, little have been reported about the effect of surgeries on the improvement of disease activity and activity of daily living. Objectives: We aimed to investigate the influence of upper extremity surgeries on the improvement of disease activity, upper extremity function, and activity of daily living in patients with rheumatoid arthritis. Methods: Between January 2009 and December 2012, 52 procedures (15 elbows, 23 wrists, and 14 hands) of 48 patients were included for this study with at least 6 months follow-up. Mean age at the surgery was 59.8 years, mean disease duration was 17.9 years, and mean follow-up period was 18.7 (range; 6-41) months. Dosage of corticosteroid (mg/day) and methotrexate (mg/week) were 4.9±4.4, and 3.1±3.3, respectively. 25% of the patients were under control of biologic agents. Visual Analog Scale for pain (VAS), Health Assessment Questionnaire - Disability Index (HAQ-DI), Disability of Arm, Shoulder, and Hand (DASH) score, and DAS28-CRP were assessed in all patients before surgery and at the final follow-up, and calculated the value of change of these clinical parameters, i.e. ΔVAS, ΔHAQ, ΔDASH, and ΔDAS. Statistical analysis was performed by Wilcoxon signed rank test and Spearman's rank correlation coefficient. Results: Before surgery, VAS, HAQ-DI, DASH, and DAS28-CRP were 37.7±25.6, 0.84±0.58, 44.0±21.0, and 2.93±0.95, respectively. At the final follow-up, VAS, HAQ-DI, DASH, and DAS28-CRP were 23.1±20.8, 0.83±0.73, 33.4±21.7, and 2.29±0.94, respectively. VAS (p<0.001), DAS28-CRP (p<0.001), and DASH score (p<0.001) significantly improved after surgery. HAQ-DI significantly correlated with VAS (r=0.34, p<0.05), DASH (r=0.78, p<0.001), and patients' age (r=0.31, p<0.05) at the final follow-up. HAQ-DI did not improved, although significant correlation were detected between ΔHAQ and ΔDAS (r=0.29, p<0.05). In daily activities, items for doing heavy household chores, washing or blowing one's hair, and feeling less capable, less confident, and less useful were improved by surgery. Conclusions: The results of the current study showed that elbow, wrist, and hand surgery could improve VAS, function of upper extremity, as well as disease activity. HAQ-DI did not improve after surgery, probably because the progression of dysfunction of other joints due to RA and decreased physical function associated with aging. References: Angst F, John M, Pap G, Mannion AF, Herren DB, Flury M, Aeschlimann A, Schwyzer HK, Simmen BR. Comprehensive assessment of clinical outcome and quality of life after total elbow arthroplasty. Arthritis Rheum 2005;53:73-82. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4791